1998
DOI: 10.1046/j.1365-2265.1998.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of IGF‐I and IGFBP‐3 to therapeutic intervention in children and adolescents with Crohn's disease

Abstract: The IGF system, as shown by serum IGF-I and IGFBP-3, is responsive to therapeutic intervention in active Crohn's disease. It is likely that a combination of decreased inflammatory activity and improved nutrition contributes to these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
1
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 33 publications
6
68
1
6
Order By: Relevance
“…Based on previous studies in adults with inactive Crohn disease, it was hypothesized that adolescents with inactive Crohn disease would be anabolic, decreasing proteolysis and increasing protein synthesis in response to enteral feeding (8). This hypothesis is supported by reports that Crohn disease remission is associated with improvement of growth and of hormonal and metabolic processes promoting accrual of lean body mass (11)(12)(13). However, previous studies have shown that in adolescents with inactive Crohn disease energy expenditure is increased as compared with healthy adolescents (14), and deficits in lean body mass persist during remission (15).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Based on previous studies in adults with inactive Crohn disease, it was hypothesized that adolescents with inactive Crohn disease would be anabolic, decreasing proteolysis and increasing protein synthesis in response to enteral feeding (8). This hypothesis is supported by reports that Crohn disease remission is associated with improvement of growth and of hormonal and metabolic processes promoting accrual of lean body mass (11)(12)(13). However, previous studies have shown that in adolescents with inactive Crohn disease energy expenditure is increased as compared with healthy adolescents (14), and deficits in lean body mass persist during remission (15).…”
supporting
confidence: 54%
“…One participant had a history of treatment with prednisone (10 mg) during the month the study was performed. Crohn disease severity was assessed by using the previously validated Pediatric Crohn's Disease Activity Index (PCDAI), with PCDAI scores categorized as follows: quiescent disease (0 -10), mild disease activity (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), moderate to severe disease activity (Ͼ30) (16). The mean PCDAI was 8 Ϯ 9 [standard deviation (SD)] and range was 0 -25, indicating quiescent to mild disease activity in all subjects at the time of evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…16 Studies in IBD patients have clearly demonstrated that the reduction in systemic inflammation following various therapeutic strategies is associated with an increase in plasma IGF-1 and IGFBP-3 levels. 17,18 Furthermore, the anti-inflammatory properties of steroids overcome even their adverse effect on the GH/IGF-1 axis at hypothalamic, pituitary and target organ levels. 18 However, notwithstanding the widespread use of anti-TNF-a treatment in IBD patients, no data are available concerning its effect on the GH/IGF-1 axis.…”
mentioning
confidence: 99%
“…Aproximadamente 20% dos pacientes ficaram com altura final mais de 8 cm abaixo do alvo familiar, sendo mais comprometidos aqueles que já apresentavam baixa estatura no diagnóstico da doença e aqueles com comprometimento de jejuno (41). A suplementação nutricional adequada e a ressecção cirúrgi-ca da porção intestinal acometida levam à melhora do crescimento, porém alguns pacientes não conseguem recuperar totalmente o crescimento (42). Alguns estudos têm demonstrado os efeitos do tratamento com GH nestes pacientes.…”
Section: Doença De Crohnunclassified